1996
DOI: 10.1128/aem.62.5.1630-1635.1996
|View full text |Cite
|
Sign up to set email alerts
|

Glucanolytic Actinomycetes Antagonistic to Phytophthora fragariae var. rubi, the Causal Agent of Raspberry Root Rot

Abstract: A collection of about 200 actinomycete strains was screened for the ability to grow on fragmented Phytophthora mycelium and to produce metabolites that inhibit Phytophthora growth. Thirteen strains were selected, and all produced ␤-1,3-, ␤-1,4-, and ␤-1,6-glucanases. These enzymes could hydrolyze glucans from Phytophthora cell walls and cause lysis of Phytophthora cells. These enzymes also degraded other glucan substrates, such as cellulose, laminarin, pustulan, and yeast cell walls. Eleven strains significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(49 citation statements)
references
References 39 publications
2
43
0
4
Order By: Relevance
“…Phytophthora fragariae (Valois et al 1996) and P. aphanidermatum (El-Tarabily 2006). Pythium hyphae have been reported to contain mainly the noncellulosic b-1,3-and b-1,6-linked glucans as the predominant glucans in addition to the cellulosic b-1,4-linked glucan, which are present as a relatively small proportion of the total glucans (Sietsma et al 1975).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Phytophthora fragariae (Valois et al 1996) and P. aphanidermatum (El-Tarabily 2006). Pythium hyphae have been reported to contain mainly the noncellulosic b-1,3-and b-1,6-linked glucans as the predominant glucans in addition to the cellulosic b-1,4-linked glucan, which are present as a relatively small proportion of the total glucans (Sietsma et al 1975).…”
Section: Discussionmentioning
confidence: 99%
“…(El-Tarabily 2006) and Phytophthora spp. (Valois et al 1996). It is also interesting that production of siderophores was not involved as a mechanism of biocontrol, although siderophore-mediated competition for iron has been reported to be an important mechanism of biological control of Pythium diseases by bacterial antagonists (Matthijs et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…are generally saprophytic, soil-dwelling microorganisms that spend the majority of their life cycle as spores. It has also been demonstrated that actinomycetes are important microorganisms in the rhizosphere and their antagonism to phytopathogenic fungi has been demonstrated [1]. Some actinobacteria are also known to inhabit the tissues of healthy plants.…”
Section: Introductionmentioning
confidence: 99%